The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3354/meps10016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fishing, market price, and climate on two South American clam species

Abstract: Coastal shellfish are being threatened by several drivers acting at multiple temporal and spatial scales, including fishing, climate, and globalization of markets. We evaluated largescale and long-term combined effects of fishing, climate, and economic variables on 2 congeneric clams that inhabit sandy beaches of the Pacific (Mesodesma donacium) and the Atlantic (M. mactroides) in South America. Bioeconomic and climatic variables, such as coastal sea surface temperature anomalies (SSTA) and broad-scale climati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 68 publications
3
66
0
9
Order By: Relevance
“…In cases such as this, where biomass fluctuations are the norm, it seems that the cost of maintaining effective governance systems may be higher than the benefits over time, leading inexorably to SES collapse. Even though mass mortalities have been described for this resource (Riascos et al 2009), and suggestions have been made that this may have swamped existing management measures (Ortega et al 2012), this was not the case for M. donacium in Tongoy Bay. Although the population was decimated in Coquimbo with the ENSO in 1997-1998, the population in Tongoy was not affected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases such as this, where biomass fluctuations are the norm, it seems that the cost of maintaining effective governance systems may be higher than the benefits over time, leading inexorably to SES collapse. Even though mass mortalities have been described for this resource (Riascos et al 2009), and suggestions have been made that this may have swamped existing management measures (Ortega et al 2012), this was not the case for M. donacium in Tongoy Bay. Although the population was decimated in Coquimbo with the ENSO in 1997-1998, the population in Tongoy was not affected.…”
Section: Discussionmentioning
confidence: 99%
“…Among the resources managed through the AMERB system in Chile is the surf clam, known as "macha." Fluctuations in landings of surf clams are a common feature of these fisheries worldwide (McLachlan et al 1996), making the sustainability of this fishery difficult to achieve (Ortega et al 2012). This variability reflects fluctuations in the population size, which is related to highly variable levels of recruitment and mortality de Alava 1995, McLachlan et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In the southwestern Atlantic Ocean, long-term trends in abundance of the yellow clam (Mesodesma mactroides) were negatively affected by a combined effect of increasing SSTA and fishing intensity (Ortega et al 2012). SSTA was positively correlated with AMO variations and both indices were inversely correlated with yellow clam abundance (Fig.…”
Section: Shellfisheriesmentioning
confidence: 95%
“…Indeed, a recent evaluation of the surf clam (Mesodesma donacium) in the Pacific (distribution range from 5ºS to 42º S) suggested that warm ENSO (El Niño) events negatively affected landings in Peru and northern Chile (Fig. 1A), but favored landings in southern Chile (southernmost edge of the species distribution), showing a positive correlation with increasing sea surface temperature anomalies (SSTA; Ortega et al 2012). Particularly in Peruvian beaches, the strong 1982/1983 and 1997/1998 El Niño events caused mass mortalities of surf clam (Arntz et al 1987).…”
Section: Shellfisheriesmentioning
confidence: 99%
“…Various causes have been identified for MMB outbreaks, including: high sea temperatures and heat waves (Cheney et al 2000, Ortega et al 2012, Rodrigues et al 2015; changes in salinity (Xiao et al 2005), turbidity, and pH; high primary production (Cheney et al 2000, Mydlarz et al 2006; eutrophic waters (Friedman and Hedrick 1991); invasive species as competitors or predators (Matsuyama 1999, McKindsey et al 2007; pathogens (Elston et al 1987); and density-dependent factors (Brazeiro andDefeo 1999, Xiao et al 2005).…”
Section: Review Of Literaturementioning
confidence: 99%